Insect pest management in vegetable crops through trap cropping: Review - PANWAR, LALITA; DEVI, SUMAN; SINGH, YASHDEV (The Indian Journal of Agricultural Sciences, 2021)
The study was carried out at CCS Haryana Agricultural University, Hisar during 2019 as the widespread use ofinsecticides to control crop pests has created various problems such as residues in the food chain, phytotoxicity,pesticide resistance, pest resurgence, bioaccumulation and secondary pest outbreak, in addition to causing harmfuleffect on the environment and non-targeted beneficial organisms. However, trap cropping is one such type of specialcompanion planting strategy that is traditionally used for insect pest management through vegetative diversificationused to attract insect pests away from the main crops during a critical time period by providing them an optionalpreferred choice. Trap cropping also has a tremendous potential to attract and conserve natural enemies in croppingsystems. The effect of attracting natural enemies may be an advantage compared to the other/conventional meansof pest control. Trap cropping can be integrated with other Integrated Pest Management (IPM) tactics. But trapcropping, like many other cultural tactics, remains under-exploited. Research on trap cropping has been very limited,and deserves more consideration to sustain agro-ecosystems throughout the world. In this review we have providedinformation based on trap cropping modalities and an updated list of trap cropping system in vegetable crops thatshould be proven as helpful in future trap cropping endeavors.